1976
DOI: 10.2307/1540509
|View full text |Cite
|
Sign up to set email alerts
|

OSMOTIC ADJUSTMENT IN AN ESTUARINE POPULATION OFUROSALPINX CINEREA(SAY, 1822) (MURICIDAE, GASTROPODA)

Abstract: Individuals from a subtidal, estuarine population of the common oyster drill, Urosalpinx cinerea (Say, 1822), were brought into the laboratory and tested for osmotic adjustment to changing salinity. Tissue variables monitored at seven experimental salinities ranging from 10 to 40% were tissue fluid osmolality, chloride, sodium, potassium, free amino acids (FAA), ninhydrin-positive substances (NPS) and water content. The results of this study demonstrate that the test animals did not exhibit anisosmotic regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Only three other studies are available, (exclusively assessing molluscs) that measured inorganic as well as organic compounds after longterm low-salinity acclimation. Similar to our results, these studies found significant effects of salinity on both osmolyte pools and a larger inorganic pool size (Potts, 1958;Turgeon, 1973;Silva, 1992).…”
Section: Cellular Osmoregulationsupporting
confidence: 90%
“…Only three other studies are available, (exclusively assessing molluscs) that measured inorganic as well as organic compounds after longterm low-salinity acclimation. Similar to our results, these studies found significant effects of salinity on both osmolyte pools and a larger inorganic pool size (Potts, 1958;Turgeon, 1973;Silva, 1992).…”
Section: Cellular Osmoregulationsupporting
confidence: 90%
“…Certainly the recent literature supports this generalization. Several authors have investigated the effects of salinity changes on the osmotic and ionic concentrations of the extracellular fluid and all of these studies have indicated that the snails were essentially isosmotic/isionic over the tolerated salinity ranges (Todd, 1964a, b;Turgeon, 1976;Avens and Sleigh, 1965). There are, however, exceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have demonstrated a decrease in the FAA pool of prosobranch gastropods following transfer to dilute media (Staaland, 1970;Turgeon, 1976;Negus, 1968;Ivanovici et al 1981;Bedford, 1971a) whereas other species have shown no such decrease (Emerson, 1969;Peterson and Duerr, 1969). The total concentration of the FAA pool in A. crenata is comparable to other marine and estuarine molluscs studied (Simpson et al, 1959;Peterson and Duerr, 1969;Turgeon, 1976); however, previous studies have shown that the total concentration of the FAA pool is attributable to only a few individual FAA (Gly, Ala, Pro, Glu, Tau, Asp, Glutamine) with Gly and Ala sometimes constituting up to 50% of the total concentration. We have demonstrated here that A. crenata utilizes the FAA pool in osmotic regulation when exposed to dilute media (Tables I, II).…”
Section: Discussionmentioning
confidence: 99%
“…In Tegula funebralis, ninhydrin-positive substances were found in greater concentrations in the whole body of animals living in sea water than in 50% sea water (Peterson & Duerr, 1969); but the snails in 50% sea water may well have been showing sublethal effects, since they had a high mortality rate. In Urosalpinx cinerea, taurine concentrations in the whole body decreased by 50% when the snails were transferred from 100% to 50% sea water (Turgeon, 1976). In Buccinum undatum, ninhydrin-positive substances were halved in 50% sea water compared to 100% sea water (Staaland, 1970).…”
Section: Terrestrial Prosobranchsmentioning
confidence: 96%
“…In Urosalpinx, the water content of the whole animal increased gradually from 40 %o to 10 %o (Turgeon, 1976). In Urosalpinx, the water content of the whole animal increased gradually from 40 %o to 10 %o (Turgeon, 1976).…”
Section: Terrestrial Prosobranchsmentioning
confidence: 97%